PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA DENGAN DISIPLIN PEGAWAI SEBAGAI VARIABEL INTERVENING PADA KANTOR DIREKTORAT JENDERAL KESEHATAN MASYARAKAT KEMENTERIAN KESEHATAN - Ahmadi; Sitorus, Guston; Siagian, Arifin (Pasca Sarjana Universitas Satya Negara Indonesia, 2023)
Performance is an important key to the success of an organization, agency or company. Maximum and optimal performance will deliver the entity to the goals set. Organizational performance is highly dependent on individual performance which is influenced by many aspects. The Directorate General of Public Health is the main unit in the Ministry of Health which is responsible for efforts to promote health and community empowerment, nutrition and maternal and child health, health for productive age and the elderly and mental health as well as public health governance. With this main function, the Directorate General of Public Health is the spearhead of health services organized by the state. The Directorate General of Public Health is also inseparable from performance measurement. This study aims to determine the effect of employee competence, compensation and discipline on performance with employee discipline as an intermediary variable. The method used is a quantitative method through a cross sectional approach. The study used a total sampling of 85 respondents and data processing used path analysis and regression analysis. The results of the study show that competence has an effect on employee discipline, compensation has no effect on employee discipline, competence has no significant effect on employee performance, compensation has no effect on employee performance, employee discipline has an effect on employee performance, employee discipline has no significant mediating effect of competence on employee performance, but significantly mediates the effect of compensation on employee performance.